Screening for Obstructive Sleep Apnea in Primary Care - Koutsokalis, Frances (My University, 2019)
Despite efforts to improve health and reduce morbidity and mortality rates, health screenings for significant conditions such as obstructive sleep apnea (OSA) are often missed. It is estimated that 80% of OSA cases remain undiagnosed and that early identification and treatment are vital for preventing health complications of OSA. Focusing screening efforts by primary care providers could be key in identifying and treating these patients. The purpose of this quality improvement project was to routinely screen all patients seen in a primary care clinic over a ten-week period using the STOP-Bang questionnaire to identify patients at risk for OSA. A total of 575 STOP-Bang questionnaires were completed, 256 (44.5%) of which identified patients at moderate to high risk leading to 19 sleep studies being ordered. Overall staff compliance rate was 77.1% with screening efforts, which was monitored weekly. Ultimate goals of the project were to improve patient care, outcomes, and overall health. Screening for OSA in primary care can be an effective way to identify at-risk individuals and improve health outcomes. Instilling a sense of significance and confidence in health care staff members is crucial to success of routine screening.
Keywords: Obstructive sleep apnea, standardized screening, staff education, STOP Bang questionnaire, sleep apnea, OSA, primary care